THE COMMODIFICATION OF RELIGION IN AINIQUA MINERAL WATER PRODUCTS IN MEDAN CITY - Muhammad Safitrah; Muhammad Jailani (Program Pascasarjana UIN Sumatera Utara, 2026)
The phenomenon of religious commodification in consumer products is increasingly evident through the use of religious symbols, narratives, and identities as marketing strategies. This study aims to analyze the process of religious commodification in Ainiqua mineral water products in Medan City and identify factors that hinder its implementation. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of four people, consisting of Ainiqua managers, production heads/workers, religious leaders, and consumers in Medan City. The analysis was conducted by referring to Vincent Mosco's commodification theory and Theodor Adorno's cultural industry theory. The results show that religious commodification in Ainiqua products occurs through three main forms. First, content commodification is seen in the use of the